Examining the Impact of Workload, Compensation, and Work Environment on Employee Job Satisfaction: A Study at the Department of Transportation, Binjai City - Jopan Andianto Hulu; Kiki Farida (Lembaga Riset dan Inovasi Al-Matani, 2025)
This research was conducted at the Binjai City Transportation Agency with the aim of the research to determine the effect of workload, compensation and work environment partially and simultaneously on employee job satisfaction at the Binjai City Transportation Agency. The population is 75 permanent employees and the sampling is done with saturated samples so that the number of samples is 75 respondents. The type of data used is primary data and the data source used is secondary data, data collection techniques using literature studies, surveys and observations. Data analysis techniques are multiple linear regression, classical assumption tests and hypothesis tests. The results of the study are that workload, compensation and work environment partially and simultaneously affect employee job satisfaction at the Binjai City Transportation Agency. There is a strong correlationbetween workload, compensation and work environment with employee job satisfaction. Employee job satisfaction in the company can be explained by workload, compensation and work environment by 45.5% and the remaining 54.5% can be explained by other variables not studied.